Intertextuality strategies in the Diwan of Wild Lilies by Yahya Al-Samawi - Yousif, Raghda Ghassan; Al-Najjar, Ashwaq Mohammed Ismaiel (Al-Adab Journal, 2022)
The purpose of this research, which describes the strategies of intertextuality found in the Diwan of Wild Lilies by Yahya Al-Samawi, is to study the concept of intertextuality strategy between the ancient and modern, aslo clarifying its sources and forms, and differentiating between the two types of intertextuality. The direct intertextuality strategy which also includes two branches: The direct internal intertextuality, and the external direct one. The internal one means the intertextuality of phrases, structures and forms of the quatrains verses themselves whilst the external intertextuality strategy means the consistency of phrases and structures in the whole Diwan or it sometimes means the obvious influence of another poetic structure of another poet on these phrases and forms. The other type of intertextual strategies is the indirect one which means the intertextuality of ideas and meanings, templates and techniques. This type denotes the consistency of title, lines, numbers, quadrilateral templates with the text, and even the intertextuality of the used language itself. This research leads us to an end that intertextuality is an important element of composing the quatrains in the Diwan of Wild Lilies and also of maintaining its consistency and its coherent parts. We can also conclude out of this research, that these quatrains found in Wild Lilies have derived some of its intertextual strategies from The Holy Quran, which has increased its aesthetics even more. The strategy of templates and technical intertextuality is considered as one of the most common types of intertextuality used in the quatrains of Wild Lilies, and that’s due to the deep connection existed between the textual units and their own harmonic connotations. The language of the poet Yahya al-Samawi in his quatrains he used in Wild Lilies is considered as a high elevated and refined language because he used rhetorical and eloquent techniques such as simile, metaphor, and metonymy. Also, it’s considered a very creative language because he used poetic tools such as counterparts, alliteration, assonance, puns and more… He used the classical language, which is a language nearer to the inimitable simplicity mixed with eloquence and full of poetic imagination, void of verbal complexity and emphasizing on the use of soft speech, and furthermore, avoiding as much as possible the use of dictionary words without allowing any linguistic displacement to take place.